Ahara vidhi – the Ayurvedic dietary concepts: Array - Sahu, Jyoti Bala; More, Anand B. (Ayurline: International Journal of Research in Indian Medicine, 2019)
The aim of Ayurved is to maintain the health of healthy person and cure from diseases. In present era, diet and life style are responsible for many diseases. According to Ayurved the living human body and diseases that afflict it is both the product of Ahara. Ahara is considered as one of the Tri upastambha of life. So many guidelines are explained in Ayurvedic texts, which are titled as AharaVidhi, where the laws of do’s and don’ts about diet and drinks are given. At the presents many newer food processing methods are in practices which are harmful to human being. That’s why Ayurved suggest that one should follow these guiding principles to prevent various diseases. Ayurved offers some basic dietary guidelines that include choosing appropriate food, combination of food, cooking methods, quality and quantity of food, nature of consumer, geographical and environmental conditions etc. On this background this review will be helpful to adopt the dietary directives in the day to day life.